Irrigation decision-making processes and conditions: a case study of Sri Lanka's Kirindi Oya Irrigation Settlement Project - Nijman, C. (International Irrigation Management Institute, 1992)
Detailed study of decision-making processes and managerial conditions of the Kirindi Oya Irrigation and Settlement Project in Sri Lanka, adopting a management perspective in the analysis of the performance of this major irrigation system in Sri Lanka. This paper is a companion document to "Irrigation management processes and conditions" by the same author.